Results of the surgical treatment of diffuse pigmented villonodular synovitis (diffuse-type tenosynovial giant-cell tumor) of the knee - S. I. Herasymenko; O. A. Kostogryz; Yu. O. Kostogryz; A. M. Babko; V. M. Mayko (Zaporožskij Medicinskij Žurnal)
The aim. To develop a treatment algorithm with the aim of improving the treatment results of diffuse pigmented villonodular synovitis of the knee. To study and analyze the results of surgical treatment of diffuse pigmented villonodular synovitis of the knee.